2020
DOI: 10.1016/j.jvs.2019.08.285
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo expansion of regulatory T cells from abdominal aortic aneurysm patients inhibits aneurysm in humanized murine model

Abstract: Objective: Abdominal aortic aneurysm (AAA) is a chronic inflammatory disease. Studies of human aneurysm tissue demonstrate dense inflammatory cell infiltrates with CD4 þ T cells predominating. Regulatory T cells (Tregs) play an important role in inhibiting pro-inflammatory T cell proliferation, therefore, limiting collateral tissue destruction. The aim of this study was to investigate whether ex vivo augmentation of human Tregs attenuates aneurysm formation in humanized murine model of AAA. Methods: Circulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Another study showed that the proportion of Treg cells in peripheral mononuclear cells were markedly decreased in AAA patients than controls (88). The average aortic diameters of Foxp3 -/mice were larger than WTs after CaCl 2 induction, while infusion of normal Treg cells to Foxp3 -/mice can render their similar aortic size with WTs after CaCl 2 induction (88). Administration of IL-2 to expanse FOXP3 + Treg cells also reduced the incidence and mortality of AAA in Apoe -/mice with angiotensin II infusion (89).…”
Section: Regulatory T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that the proportion of Treg cells in peripheral mononuclear cells were markedly decreased in AAA patients than controls (88). The average aortic diameters of Foxp3 -/mice were larger than WTs after CaCl 2 induction, while infusion of normal Treg cells to Foxp3 -/mice can render their similar aortic size with WTs after CaCl 2 induction (88). Administration of IL-2 to expanse FOXP3 + Treg cells also reduced the incidence and mortality of AAA in Apoe -/mice with angiotensin II infusion (89).…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…Studies have shown that EX-527, an inhibitor of SIRT1, can recover the acetylation levels of FOXP3, increase the number of active Treg cells and bring (87). Another study showed that the proportion of Treg cells in peripheral mononuclear cells were markedly decreased in AAA patients than controls (88). The average aortic diameters of Foxp3 -/mice were larger than WTs after CaCl 2 induction, while infusion of normal Treg cells to Foxp3 -/mice can render their similar aortic size with WTs after CaCl 2 induction (88).…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…An array of different inflammation modifying regimens have recently been reported to inhibit or promote the incidence and/or rupture of AAAs formed in the different mouse models (Figure 2 and Table S1) (Amin et al, 2019;Hiromi et al, 2020;Krishna et al, 2019;Li, Nie, et al, 2019;Li, Xia, et al, 2019;Liu, Fitzgerald, et al, 2019;Liu, Kong, et al, 2019;Nie et al, 2019;Paige et al, 2019;Peshkova et al, 2019;Ren et al, 2020;Sharma, Dev, Belenchia, et al, 2019;Suehiro et al, 2019;Suh et al, 2020). The nucleotide-binding domain leucine-rich repeat (NLR) and pyrin domain-containing receptor 3 (NLRP3)-inflammasome plays an important role in innate immunity through controlling the secretion of pro-inflammatory cytokines.…”
Section: Assessing Outcomes In Mouse Models Of Aaamentioning
confidence: 99%
“…A large body of published research suggests that Foxp3 + regulatory T cells inhibit AAA development within both the angiotensin II and CaCl 2 models (Golledge, 2019;Liu, Kong, et al, 2019;Suh et al, 2020;Yodoi et al, 2015). Of potential clinical application, it was recently reported that ex vivo expansion and administration of Foxp3 + regulatory enriched T cells reduced the size of CaCl 2 -induced AAAs (Suh et al, 2020). One mechanism underlying the beneficial effects of regulatory cells is through inhibiting PG production by decreasing COX-2 expression (Suh et al, 2020).…”
Section: Assessing Outcomes In Mouse Models Of Aaamentioning
confidence: 99%
“…Treatment with IL-33 increased Tregs within the aorta and suppressed vascular smooth muscle cell (VSMC) chemokine expression. Suh et al also explored the role of Tregs in aneurysm development by using a humanized murine model of AAA by irradiating Rag1 −/− mice at 7 weeks of age and supplementing them with human CD4 + T-cells [ 50 ]. Rag1 −/− mice are resistant to aneurysm formation in the CaCl 2 model; however, when supplemented with human CD4 + cells, they became susceptible to AAA formation.…”
Section: Cellular Responses Of the Aortic Wallmentioning
confidence: 99%